The four known biplanes with k=11 - Chester J. Salwach; Joseph A. Mezzaroba (International Journal of Mathematics and Mathematical Sciences)
The four known biplanes of order 9(k=11) are described in terms of their ovals, λ-chain structures, and automorphism groups. An exhaustive computer search for all biplanes of order 9 with certain chain structures has produced but two, one of which is new. None of these four biplanes yield the putative plane of order 10.